Solve (d^2y)/(dx^2)+y=sec^2x
"{d^2y\\over dx^2}+y=sec^2(x)"
But "sec^2(x)=tan^2(x)+1"
Rewriting the differential equation, we have
"{d^2y\\over dx^2}+y=tan^2(x)+1......................(i)"
The corresponding homogenous linear equation is
"{d^2y\\over dx^2}+y=0........................(ii)"
To solve this homogenous linear equation "(ii)" ,Find the roots of characteristic equation
"k^2+1=0 \\implies" "k_1=-i" or "k_2=i"
The two roots of the characteristic equation are purely imaginary
"\\therefore y(x)=C_1sin(x|k_1|)+C_2cos(x|k_2|)"
"\\implies y(x)=C_1sin(x)+C_2cos(x)...................(iii)"
Equation "(iii)" is our general solution
Now we should solve the inhomogeneous equation "(i)" Using variation of parameters method
Suppose "C_1" is function of "x" and "C_2" is also a function of "x"
The general solution is:
"\\implies y(x)=C_1(x)sin(x)+C_2(x)cos(x).................(iv)"
Where "C_1(x)" and "C_2(x)" by method of variation of parameters ,we find the solution from the system
"y_1(x){d\\over dx}C_1(x)+y_2(x){d\\over dx}C_2(x)=0"
"{d\\over dx}C_1(x){d\\over dx}y_1(x)+{d\\over dx}C_2(x){d\\over dx}y_2(x)=f(x)"
Where "y_1(x)" and "y_2(x)" are linearly independent solutions of linear Ordinary differential equations and "f(x)" is the free term and are given as
"y_1(x)=sin(x)" , "y_2(x)=cos(x)" and "f(x)=tan^2(x)+1"
Substituting to the system above, we have
"sin(x){d\\over dx}C_1(x)+cos(x){d\\over dx}C_2(x)=0"
"{d\\over dx}C_1(x){d\\over dx}sin(x)+{d\\over dx}C_2(x){d\\over dx}cos(x)=tan^2(x)+1"
But "{d\\over dx}sin(x)=cos (x)" and "{d\\over dx}cos(x)=-sin(x)"
Substituting to our system, we get:
"sin(x){d\\over dx}C_1(x)+cos(x){d\\over dx}C_2(x)=0"
"cos(x){d\\over dx}C_1(x)-sin(x){d\\over dx}C_2(x)=tan^2(x)+1"
Solving the system simultaneously, We get
"{d\\over dx}C_1(x)={1\\over cos(x)}" and "{d\\over dx}C_2(x)=-{sin(x)\\over cos^2(x)}"
let's solve "{d\\over dx}C_1(x)={1\\over cos(x)}" and "{d\\over dx}C_2(x)=-{sin(x)\\over cos^2(x)}"
"{d\\over dx}C_1(x)={1\\over cos(x)} \\implies dC_1(x)={dx\\over cos(x)}"
Integrating both sides we have
"\\int dC_1(x)=\\int {dx\\over cos(x)}\\implies C_1(x)=C_3-{log(sin(x)-1)\\over 2}+{log(sin(x)+1)\\over 2}"
"{d\\over dx}C_2(x)=-{sin(x)\\over cos^2(x)} \\implies dC_2(x)=-{sin(x)\\over cos^2(x)}dx"
Integrating both sides we have
"\\int dC_2(x)=-\\int{sin(x)\\over cos^2(x)}dx\\implies C_2(x)=C_4-{1\\over cos(x)}"
Now, substitute "C_1(x)" and "C_2(x)" to the general solution "(iv)"
"y(x)=C_1(x)sin(x)+C_2(x)cos(x)"
"=(C_3-{log(sin(x)-1)\\over 2}+{log(sin(x)+1)\\over 2})sin(x)+(C_4-{1\\over cos(x)})(x)cos(x)"
"\\therefore y(x)=C_2cos(x)+(C_1-{log(sin(x)-1)\\over 2}+{log(sin(x)+1)\\over 2})sin(x)-1"
Comments
Leave a comment